Analisis Penerapan Harga Pokok Produksi (HPP) Pada Pembuatan Kapal Pinisi di Desa Ara Kecamatan Bontobahari Kabupaten Bulukumba - Inayah, Nurul; Tikollah , M. Ridwan; Ryketeng , Masdar (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the application of the cost of production in the construction of Pinisi ships in Ara Village, Bontobahari District, Bulukumba Regency. The research adopts a qualitative descriptive approach, focusing on the cost of production as a single variable. Data were collected through observation, interviews, and documentation. Data analysis was carried out by calculating the cost of production using the full costing and variable costing methods and comparing the results with the company's calculation. The results show that the cost of production using the full costing method amounted to IDR 736,241,127, the cost of production using the variable costing method amounted to IDR 731,386,127, and the company's cost of production was IDR 733,301,127. These findings highlight the importance of applying accurate cost calculation methods to reflect the total production cost and support decision-making in the Pinisi shipbuilding process.